Model-based motion control for multi-axis servohydraulic shaking tables. (August 2016) - Plummer, A.R.
Abstract: The shaking table is an essential testing tool in the development of earthquake resistant buildings and infrastructure, so improving its performance is an important contribution to saving lives. Currently the bandwidth and accuracy of shaking tables is such that earthquake motion often cannot be replicated with the desired fidelity. A new model-based motion control method is presented for multi-axis shaking tables. The ability of this method to decouple the control axes is demonstrated. A linear parameter varying modal control approach is used – i.e. the modes of vibration of the system are controlled individually, with the modal decomposition repeated at each time step to account for parameter variations. For each mode, a partial non-linear dynamic inversion is performed in the control loop. Feedback is based on a combination of position and acceleration measurements. A command feedforward method is proposed to increase the tracking bandwidth, thus the controller has a two degree-of-freedom structure. Experimental and simulation results are presented for a large (43 t total) six degree-of-freedom shaking table. The simulation results are based on a detailed, validated model of the table. Experimental results show that the controller gives exceptional performance compared a conventional proportional controller: for example the horizontal acceleration bandwidth is six-times higher at over 100 Hz, which is also many times higher than the hydraulic resonant frequency. These results will allow a step change in earthquake simulation accuracy. Graphical abstract: Highlights: High bandwidth shaking table control for better simulation of earthquake motion. Real-time modal decomposition used to decouple control axes. Actuator-stiffness related modal dynamics are cancelled within the control loop. Experimental results shown for a 43 tonne overconstrained 6 DOF shaking table. Acceleration bandwidth is 100Hz, much higher than hydraulic resonant frequencies.